Hadis amalan terbaik dalam Sahih Bukhari: analisa stilistik fonosemantik = Hadiths of the exemplary practices in Sahih Bukhari: a phonosemantic stylistic analysis - Ahmad, Hishomudin; Ahmad Ghafar, Norfarhana; Ahmad, Muhammad Anwar; Ku Yaacob, Ku Mohd Syarbaini (USIM Press, 2024)
Stylistics, a sub-discipline of applied linguistics, examines the aesthetic aspects of language style within texts, particularly literary ones. While it is often used to explore the linguistic beauty of the Quran, it is less frequently applied to Prophetic Hadith texts. This study aims to analyse Hadiths that contain conversations between the Prophet and his companions, known as the Qauli Hiwari-type, related to exemplary practices (Afdhal al-‘amal), in Sahih Bukhari. Textual analysis was applied using phonosemantic analysis to examine letter combinations in words and ascertain their meanings related to these practices. The findings reveal five exemplary practices in the Prophet's Hadiths as narrated in Sahih Bukhari, hierarchically arranged to reflect their significance: belief in Allah SWT and His Messenger, and performing prayers punctually, which are fundamental to Islam, followed by kindness to parents, Jihad fi Sabillillah, and performing Hajj Mabrur, subject to individual limitations and capacities. This study demonstrates that phonosemantic stylistics can effectively analyze the linguistic style of religious texts, particularly in discerning meanings embedded in letter combinations, and shows that Hadith texts can be examined through stylistics with appropriate guidelines. These findings contribute to a deeper understanding of the linguistic nuances and religious teachings within the Hadiths of Sahih Bukhari.